L’isotopie complexe comme défi traductologique - Landheer, Ronald (Wydawnictwo Naukowe UAM, 2000)
Intentional ambiguities and complex textual isotopies may be considered as essential and deliberate communicative strategies in any discourse, and as such they demand specific translational strategies. In spite of rather common apriorisms about their alleged ‘untranslatability’, mainly based on interlingual asymmetry, entirely satisfying translations are quite often possible, if one bears in mind that: a) very striking interlingual parallelisms e.g. in conceptual metaphorical and metonymical shifts are rather widespread; b) isotopies - although often entailing certain types of wordplay - always include semantic textual coherence (even if so in a plurivalent manner) to be rendered anyway; and finally, c) the notion of (un)translatability itself should not be taken in a too restrictive way. Recent developments in translation theory, as well as in linguistics and literary criticism throw new light on an old problem.
Complex isotopy as a challenge to a translator